EFFICACY AND TOLERABILITY OF DIFFERENT ORAL IRON PREPARATIONS IN IRON DEFICIENCY ANEMIA: REVIEW - Anastasiia Holoborodko; Ewa Wieczorkiewicz; Patrycja Stępińska; Eliza Garbacz; Agnieszka Pocheć; Bartosz Lautenbach; Dariusz Nędza; Klaudia Wojciech; Anhelina Loputs; Wiktoria Błaszczyk (International Journal of Innovative Technologies in Social Science, 2026)
Background: iron deficiency anemia (IDA) is a widespread, preventable condition that diminishes work capacity, cognition, and overall health. Dysregulation of iron homeostasis — principally via hepcidin‑mediated sequestration — distinguishes absolute deficiency from functional deficiency, guides diagnostic interpretation and helps to choose the type therapy.Aim: The aim of this article is to compare the available oral iron supplements with respect to efficacy, tolerability and practical use. It summarizes current evidence regarding optimal dosing and frequency of administration in individuals with iron deficiency and iron-deficiency anemia.Methods: narrative review of literature up to 2025, prioritizing recent meta‑analyses, systematic reviews, randomized controlled trials, phase III randomized studies and other high‑quality studies. Searches were conducted in PubMed/MEDLINE, Embase, Web of Science and Google Scholar. Key search terms included oral iron, ferrous sulfate, liposomal iron, sucrosomial iron, ferric maltol and ferrous bisglycinate. This review compares their efficacy and tolerability. Study selection, data extraction, and quality evaluation followed standard review procedures; findings were synthesized and summarized in tables.Results: new supplements generally achieve comparable or faster hematologic responses at lower elemental iron doses and are associated with fewer gastrointestinal side effects, which may improve adherence, particularly in patients intolerant of ferrous salts or with inflammatory conditions. Dosing approaches that account for hepcidin dynamics (alternate-day or single morning dosing) enhance absorption. Heterogeneity in study populations, dosing regimens and outcome measures limits direct comparisons.Conclusion: oral iron formulations show broadly similar efficacy; selection should prioritize tolerability, comorbidity context, and dosing strategies that optimize absorption. Individualized therapy with routine monitoring of hemoglobin and ferritin improves outcomes and adherence.